(3GdahGFO GdHGQRI hGdcGefI aj GdfYe GdXGgQI hGdHGWfIs - (3YHO GdQMef Hf CHj HcQ Hf eMeO GdNVjQj GdSjhWj, CHh GdaVd , LdGd GdOjf , J (B911 (3g`s ((3YdGA GdOjf Hf YHO dGdg Hf cGed GdTGaYi s)
(3ChdgG (B:s
(3GdMeO ddg GdPi CSHZ YdjfG fYeg XGgQI hHGWfI hHYO abO PcQ di HYV GdCYRI Cf PGcQkG PcQ dg Cfg hba Ydi cdGe ddEeGe GdfSai eVehfg Cfg PcQ ai HYV cJH GdeWhdI ai JaSjQ s
(3BNQgG (B:s
(3hfNJe gPG GdcJGH HPcQ fYeI ef fYe Gddg YdjfG aGdMeO ddg Ydi fYeg GdXGgQI hGdHGWfI Je GdJCdja HMeO Gddg s
(3Vef eLehY , JQJjHgG (B: (3ef U (B38 - (3U(B44s
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdYGTQs
(3JHUQGJ GdCUd (B:s
(3MGdI GdfSNI SjFI s
(3GdfSNI HgG JdhjK , CQVg s
Keywords: (3GdJaSjQ hYdhe GdbQBfs